Upaya Peningkatan Kualitas Produk Corrugated Box dengan Pendekatan Fault Tree Analysis (FTA) dan Failure Mode and Effect Analysis (FMEA) - Syahkhaafi, Mochammad; Ratnasari, Lisa (LPPM Universitas Pahlawan Tuanku Tambusai, 2023)
PT Kreasi Kemas Indonesia is a company that produces various types of cardboard with a make to order system. The percentage of defects in the printing process on the longway machine for the 2022 production period is 2.16% of the 2% set by the company. The Fault Tree Analysis (FTA) and Failure Mode and Effect Analysis (FMEA) approaches are combined to determine the causes of defects and 5W + 1H as an improvement method. The purpose of this study is to determine the causes of defects and provide suggestions for improvement. The results showed that the causes of the largest defects with the highest RPN values were missed trial print inspection (720), imprecise sheet side clamp settings (576), and non-standard trial print (630). The recommended improvement suggestions are to conduct a more detailed and comprehensive review and sorting process during the trial printing process, provide regular socialization and assistance regarding quality assurance policies that can refer to ISO 9001: 2015 to operators, and conduct routine maintenance of all machine components